Programming with C++ - Hubbard, J. R.; Kahate, Atul; Baxter, Anthony Q. (New Delhi Tata McGraw-Hill Education Private Limited, 2009)
A crash course that includes fully solved problems for every topic, expert tips for mastering Programming with C++, and all you need to know to pass the course.
"Based on Schaum's outline of programming with C++."
Includes index.
Keywords: C++ (Computer program language)